Iron-based Layered Double Hydroxides aiming biomaterials: structure, composition, and polymer composites - Figueiredo, Mariana Pires (2021)
Layered Double Hydroxides (LDHs) are considered promising materials to compose pharmaceutical formulations and medical devices mainly by their capacity to act as carriers for anionic bioactive species. LDHs are mostly composed by Mg2+ and Zn2+ as divalent cations and Al3+ (exogenous) as trivalent cation. The substitution of aluminium by an endogenous metal, such as Fe3+, is of great interest for the development of even more promising LDHs for acting as biomaterials. However, the Fe3+ incorporation into the LDH structure has led to impure materials, also the intercalation of organic anions into these materials has been challenging. In this regard, the present work deals with two main aims: 1) to improve the applicability of Fe3+-LDH materials by the comprehension of their structure, composition, and properties; and 2) to develop advanced polymeric medical devices, such as implantable surgical membranes and therapeutic wound dressings, based on pure Fe3+-LDH phases. Concerning aim number 1), in the first part of the thesis it was investigated the effect of Fe3+ in the formation of LDH phase and the limit of aluminium substitution by iron allowing the isolation of pure LDH phases also capable to intercalate bioactive species. First, two series of Mg2FeyAl(1-y)(OH)6-Cl and Zn2FeyAl(1-y)(OH)6-Cl LDHs, intercalated with chloride anions, with y equal to 0, 0.25, 0.50, 0.75, or 1 were studied. Then, all pristine LDH-Cl materials were submitted to ion-exchange of Cl- by anions derived from the non-steroidal anti-inflammatory drug naproxen (NAP), a model organic compound. Lastly, LDH materials with nominal layer compositions Mg2FeyAl(1-y)(OH)6 and Zn2FeyAl(1-y)(OH)6, with y equal to 0, 0.25, 0.5, 0.75, or 1, aiming carriers for bioactive species were also prepared by the coprecipitation (one-pot) method in the presence of abietate anions (ABI), derived from abietic acid, a natural product that presents several biological properties (i.e. bactericidal, fungicidal, anti-inflammatory). Along each series of materials, phase purity was evaluated using several analytical techniques combined with a crystal-chemical and geometrical reasoning that allowed the comparison between the composition of the bulk samples (considering the possible contribution of amorphous phases other than LDH) and the composition of the respective crystalline LDH phases. In general, phase purity was achieved for y values lower or equal to 0.5, which corresponds to half of the Al3+ content substituted by Fe3+. Compositions considered pure and able to intercalate NAP or ABI organic anions in satisfactory amounts (i.e. the weight of the organic anion representing more than 25 % of the weight of the hybrid organic-inorganic LDH) were selected to compose polymeric devices according to the aim number 2) of this thesis, i.e. Mg2Fe0.5Al0.5(OH)6 and Zn2Fe0.5Al0.5(OH)6 layer compositions intercalated with Cl-, NAP, or ABI anions. Approaches for the modulation of the release rate of the bioactive species intercalated into LDHs were explored and in vitro cytotoxicity assays were performed as a function of the composition of the materials. Polymeric membranes were prepared by different methods: electrospinning or casting. LDHs showed promising as components of the medical devices providing advantages from the mechanical, pharmacological, and biological points of view in comparison to the polymer-drug systems. The results presented in this thesis, which include detailed structural analyses, the synthesis of several Fe3+-LDH materials able to intercalated bioactive species, as well as the development of promising polymeric membranes containing Fe3+-LDHs, are expected to advance even more the applicability of LDH as biomaterials.